Kejahatan Kekerasan Dan Brutalisme Massa (Perspektif Kriminologi) - Yulianis Safrinadiya Rahman (Al-Adl : Jurnal Hukum, 2022)
Indonesia is a country based on the rule of law, not mere power. This statement is explicitly stated in the general explanation of the 1945 Constitution of the Republic of Indonesia. This shows that Indonesia is a state of law, and as a state of law, Indonesia accepts law as an ideology to create order, security, justice, and welfare for its citizens. The criminal law currently in force in Indonesia is a codified criminal law, i.e. most of it and the rules have been compiled in a single law called the Criminal Code. Crime is an act that violates ethics and morals so that a crime committed by an offender has a detrimental impact on other people as legal subjects. Crimes of violence and mass brutalism that are occurring in Indonesia at this time are concerning and the causes and solutions must be found immediately. Because usually, the victims are the people themselves. Especially on mass brutalism, which has a very large impact on the destruction of the legal system that has been built. The research method used in this study is normative legal research because it is carried out by analyzing the library materials or based on those taken from secondary data as a reference for research in a way that is taken based on regulations and literature related to the problems studied. The normative legal research includes research on legal systematics, research on the level of legal synchronization, research on legal history, and research on comparative law. Society is a very free meaning, they have its own orderly and natural system. Behavior, actions, and conflicts will change naturally and cannot be forced, people will interpret the law through meanings that can be captured by each flow of change, and the way they interpret is different from what is interpreted by legal experts, policymakers, or conglomerates, policies can just be evil, good can be deceit, and justice can become greed, the law cannot be seen as something genuine but contains the interests of certain groups. Whereas the press and other media are like the inspiration for crime, it must be remembered that in a dynamic social system, print and film media are an integral and urgent part of the community development process.